Performance of mycelial biomass and exopolysaccharide from Malaysian Ganoderma lucidum for the fungivore red hybrid Tilapia (Oreochromis sp.) in Zebrafish embryo - Taufek, Norhidayah Mohd; Harith, Hanis H.; Abd Rahim, Muhamad Hafiz; Ilham, Zul; Rowan, Neil; Wan-Mohtar, Wan Abd Al Qadr Imad (Elsevier, 2020)
Natural mycelial biomass (MB) and extracted exopolysaccharide (EPS) from the pre-grown Malaysian Ganoderma lucidum mushroom are both considered as high-end materials due to their high commercial value in the aquaculture industry. To evaluate their potential toxicity as a fish-feed supplement for the fungivore red hybrid Tilapia (Oreochromis sp.), both MB (250−5000 μg/mL) and EPS (62.5−3000 μg/mL) were subjected to zebrafish embryo toxicity (ZFET) assay, and the effects on zebrafish embryos (ZE) early development were analyzed between 24−120 hours of post-exposure (HPE). MB and EPS showed no toxic effect towards the ZE with LC50 of 1650 μg/mL and 2648.38 μg/mL, respectively. MB at concentrations between 250−5000 μg/mL and EPS at 3000 μg/mL showed no significant changes in ZE hatching. No significant changes in the ZE heart rate were detected following treatment with both tested compounds (MB: 250−2000 μg/mL and EPS: 62.5−3000 μg/mL) as compared to untreated embryos (135.5 beats/min). Furthermore, teratogenic effects of both MB and EPS (<3000 μg/mL) on zebrafish embryonic development were not observed. Together, both natural compounds MB and EPS can be considered non-toxic, suggesting that these can be safely applied as feed substances in the fish-feed aquaculture industry. © 2020 The Authors